Políticas do estado de Minas Gerais para bibliotecas públicas (1983-2012) - Marina Nogueira Ferraz (2015)
This research aims to describe and analyze the policies for public libraries of Minas Gerais, to understand the possible advances and retreats of these policies from 1983 to 2012. Its specific objectives are to identify government policies for public libraries through acts legal and administrative documents; know the actual implementation of such policies through interviews and track possible progress or setbacks provided by policies implemented for public libraries. Justified this research in that, searching public libraries within the public policy context can serve as an important support for public managers to program new shares, contributing to the study of the social role of information and cultural policies in the field Information Science. The methodology used was documentary analysis, by means of the documents content analysis, and also carrying out semi-structured interviews with managers of the Superintendência de Bobliotecas Públicas de Minas Gerais. The theoretical basis came from the concepts and propositions of the UNESCO Manifesto for public libraries and the work done by Paiva (2008), about federal policies for the area of libraries, books and reading. At the end, we found that policies for public libraries in Minas Gerais have advanced, albeit timidly, and that the history of policies already carried out are configured, greatly, as Government policies, not as State policies.